Relationships Between Personality Features and the Rubber Hand Illusion: An Exploratory Study - Burin, Dalila; Pignolo, Claudia; Ales, Francesca; Giromini, Luciano; Pyasik, Maria; Ghirardello, Davide; Zennaro, Alessandro; Angilletta, Miriana; Castellino, Laura; Pia, Lorenzo (Frontiers in Psychology, 2019)
The rubber hand illusion paradigm allows investigating human body ownership by inducing an illusion of owning a life-sized fake hand. Despite the wide consensus on the fact that integration of multisensory signals is the main interpretative framework of the rubber hand illusion, increasing amount of data show that additional factors might contribute to the emergence of the illusion and, in turn, explain the strong inter-individual differences of the illusory patterns. Here, we explored whether and how personality features contribute to the emergence of the illusion by administering to healthy participants the rubber hand illusion paradigm along with two well-known personality tests, i.e., the Personality Assessment Inventory (PAI) and the Rorschach test. Results showed that two Rorschach domains (i.e., “Perception and Thinking Problems” and “Self and Other Representation”) were positively correlated with the illusory mislocalization of the own left hand towards the fake hand. Further analyses suggested that while the tendency to perceive unconventionally is related to mislocalizing the own hand towards the fake hand, the association of the RHI index and other personality features measured by the Rorschach remain uncertain. However, our findings in general suggest that personality features might have a role in the emergence of the rubber hand illusion. This, in turn, could explain the high inter-individual variability of the illusory effects.